Assessing Local Vulnerability to Climate Change in Rio de la Plata Basin, Uruguay - Bucaram, Santiago; Fernández, Mario; Renteria, Willington (Compendium: Cuadernos de Economía y Administración, 2016)
Vulnerability assessments to climate change have a long history on multidisciplinary research. The focus on constructing assessments has shifted from relying only on biophysical and climatic features toward a more integrated approach including social and economic aspects of human communities. This expansion on scope has converted assessments on useful tools to inform policy making and public expenditure on mitigation and adaptation to climate change. However, there is no consensus on the appropriate modelling to be followed given uncertainty on weighting and aggregation mechanisms. The purpose of this paper is to assess vulnerability to climate change at local level for the Rio de la Plata Basin in Uruguay. For this we choose a set of indicators and a methodology that can be applied to any development project and is suitable of replication to different scales, dynamics and regional diversity. Our vulnerability assessment differs from other studies in the sense that aggregation does not rely on subjective or experts-based weights but on the behavior of data. Results show north-south distribution of the most vulnerable localities in the central areas of the Basin. The vulnerability profiles are shaped mainly by adaptive capacity (in the form of access to sewage treatment systems) and hazards related to precipitation and temperature.
Keywords: Exposure, sensitivity, adaptive capacity, adaptation, mitigation